Approaches for building community participation: A qualitative case study of Canadian food security programs. (October 2017) - Hyett, Nerida; Kenny, Amanda; Dickson-Swift, Virginia
There is increasing opportunity and support for occupational therapists to expand their scope of practice in community settings. However, evidence is needed to increase occupational therapists' knowledge, confidence, and capacity with building community participation and adopting community-centered practice roles. The purpose of this study is to improve occupational therapists' understanding of an approach to building community participation, through case study of a network of Canadian food security programs. Qualitative case study was utilized. Data were semistructured interviews, field observations, documents, and online social media. Thematic analysis was used to identify and describe four themes that relate to processes used to build community participation. The four themes were use of multiple methods, good leaders are fundamental, growing participation via social media, and leveraging outcomes . Occupational therapists can utilize an approach for building community participation that incorporates resource mobilization. Challenges of sustainability and social exclusion must be addressed.